Enhancing multi-scale Mekong water governance - Lebel, L.; Bastakoti, Ram C.; Daniel, R. (CGIAR Challenge Program on Water and Food, 2010)
The CPWF Project PN50 “Enhancing multi-scale water governance” was a flagship activity of the Mekong Program on Water, Environment Resilience (M-POWER). The goal of helping improve livelihood security, human and ecosystem health in the Mekong Region through democratizing water governance was pursued through critical research and direct engagement with stakeholders involved in managing floods, irrigation, hydropower, watersheds, fisheries and urban water works at various scales. We identified commons governance problems and suggested ways that some can be addressed. Often, for example, there are needs to: strengthen local representation, improve the quality of deliberative processes, enhance the interplay between institutions at different levels, and build capacities to handle uncertainties and adapt to changes in flow regimes.